Virtual Screening, Identification and In Vitro Testing of Novel Inhibitors of O-Acetyl-L-Serine Sulfhydrylase of Entamoeba histolytica - Nagpal, Isha; Raj, Isha; Subbarao, Naidu; Gourinath, Samudrala (PLOS ONE, 2012)
The explosive epidemicity of amoebiasis caused by the facultative gastrointestinal protozoan parasite Entamoeba histolytica is a major public health problem in developing countries. Multidrug resistance and side effects of various available antiamoebic drugs necessitate the design of novel antiamobeic agents. The cysteine biosynthetic pathway is the critical target for drug design due to its significance in the growth, survival and other cellular activities of E. histolytica. Here, we have screened 0.15 million natural compounds from the ZINC database against the active site of the EhOASS enzyme (PDB ID. 3BM5, 2PQM), whose structure we previously determined to 2.4 Å and 1.86 Å resolution. For this purpose, the incremental construction algorithm of GLIDE and the genetic algorithm of GOLD were used. We analyzed docking results for top ranking compounds using a consensus scoring function of X-Score to calculate the binding affinity and using ligplot to measure protein-ligand interactions. Fifteen compounds that possess good inhibitory activity against EhOASS active site were identified that may act as potential high affinity inhibitors. In vitro screening of a few commercially available compounds established their biological activity. The first ranked compound ZINC08931589 had a binding affinity of ∼8.05 µM and inhibited about 73% activity at 0.1 mM concentration, indicating good correlation between in silico prediction and in vitro inhibition studies. This compound is thus a good starting point for further development of strong inhibitors.